Handbook of research on novel soft computing intelligent algorithms : theory and practical applications - Vasant, Pandian; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Ave., Hershey, PA, 17033) : IGI Global, 2014)
'This book explores emerging technologies and best practices designed to effectively address concerns inherent in properly optimizing advanced systems, demonstrating applications in areas such as bio-engineering, space exploration, industrial informatics, information security, and nuclear and renewable energies'--Provided by publisher.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 09/19/2013).
Keywords: Soft computing -- Industrial applications; Intelligent control systems; Intelligent agents (Computer software).; Artificial neural networks; Chaotic systems; Differential evolution; Evolutionary algorithms; Fuzzy logic; Genetic programming; Human-computer interaction; Hybrid technologies; Swarm intelligence; Team optimization